Clopidogrel Improves Skin Microcirculatory Endothelial Function in Persons With Heightened Platelet Aggregation. Issue 11 (31st October 2016) - Salimi, Shabnam; Lewis, Joshua P.; Yerges‐Armstrong, Laura M.; Mitchell, Braxton D.; Saeed, Faisal; O'Connell, Jeffry R.; Perry, James A.; Ryan, Kathleen A.; Shuldiner, Alan R.; Parsa, Afshin
Abstract : Background: Platelet activation can lead to enhanced oxidative stress, inflammatory response, and endothelial dysfunction. To quantify the effects of platelet inhibition on endothelial function, we assessed platelet activity of healthy persons before and after clopidogrel administration and evaluated its effects on endothelial function. We hypothesized that clopidogrel, by attenuating platelet activity, would result in enhanced endothelial function. Methods and Results: Microcirculatory endothelial function was quantified by laser Doppler flowmetry (LDF) mediated by thermal hyperemia (TH) and postocclusive reactive hyperemia, respectively, in 287 and 241 relatively healthy and homogenous Old Order Amish persons. LDF and platelet aggregation measures were obtained at baseline and after 7 days of clopidogrel administration. Our primary outcome was percentage change in post‐ versus preclopidogrel LDF measures. Preclopidogrel TH‐LDF and platelet aggregation were higher in women than in men ( P <0.001). Clopidogrel administration was associated with ≈2‐fold higher percentage change in TH‐LDF in participants with high versus low baseline platelet aggregation (39.4±10.1% versus 17.4±5.6%, P =0.03). Clopidogrel also increased absolute TH‐LDF measures in persons with high platelet aggregation (1757±766 to 2154±1055, P =0.03), with a more prominent effect in women (1909±846 to 2518±1048, P =0.001). There was no evidence that clopidogrel influenced postocclusive reactive hyperemia LDF measures. Conclusions: The administration of clopidogrel in healthy persons with high baseline platelet aggregation results in improved TH‐induced microcirculatory endothelial function. These data suggest that clopidogrel may have a beneficial effect on microcirculatory endothelial function, presumably through antiplatelet activity, and may confer additional vascular benefits. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00799396.